Origin narratives, origin structures, and the diarchic system of Buton kingdom, Indonesia. Issue 135 (4th May 2018) - Song, Seung-Won
ABSTRACT: This article reconstructs the history of traditional social ranks and the origin structures of the Buton sultanate in Indonesia, through an analysis of its origin narrative, Hikayat Sipanjonga . The analysis reveals that the theories of precedence and notion of origins, which are key to understanding the social structures of the Austronesian-speaking world, provide a useful interpretive tool to comprehend the dynamics of Buton's social ranking system. Of the two elite ranks, the kaomu formed the nobility from which sultans were elected, while the walaka was known as the adat group. Over the course of history, the kaomu and walaka formed a strong power alliance, and enjoyed social prestige as mutually complementary but also competitive elite groups. While the kaomu 's power was authorised by the sacred kingship and contribution to the state, the walaka 's authority was generated from its social precedence as the original source clan of Buton. Their respective roles in the kingdom reveal that the principle of diarchy – whereby the nobility took political office, and the adat group was in charge of controlling adat – was applied in Buton, yet with some deviations.